The effect of 3D silver nanodome size on hydrogen evolution activity in alkaline solution. (7th June 2018) - Yüksel, Handan; Özbay, Ayşe; Kahraman, Mehmet; Solmaz, Ramazan
Abstract: Three-dimensional (3D) Ag nanodomes (AgNDs) having different sizes (400, 800, 1200 and 1600 nm) were fabricated using combination of nanosphere lithography and soft lithography. The surface structures of 3D assembled latex particles, nanovoids and metal nanodomes (ND) were examined using scanning electron microscopy (SEM). Their heights and widths analyses were performed with the help of atomic force microscopy (AFM). The effect of diameter of the NDs on their hydrogen evolution activity was examined in 6 M KOH solution at 298 K using electrochemical techniques. Their activities were compared with the activity of bulk Ag electrode. The preparation of 3D-AgNDs having various diameters and examination of their size effects on the water splitting activity have not been studied yet and are being reported firstly. It was found that very well-structured and very uniformly distributed NDs can be fabricated using this procedure. AgNDs exhibit higher hydrogen evolution activity with respect to bulk Ag. Their hydrogen evolution activity depends on their diameters; 1200 nm NDs were the best among them. The current density at −1.40 V(Ag/AgCl) which is proportional to the rate of hydrogen releasing reaction increases from 0.70 mA cm −2 to 44.13 mA cm −2 at this ND electrode with respect to the bulk Ag electrode. At the same 3D-AgNDs electrode and potential, the resistance against the HER reduces from 148.7 Ω cm 2 to 1.12 Ω cm 2 (99.6%) by comparing with the bulk Ag electrode. The average surface roughness factors of bulk Ag, 400 nm, 800 nm, 1200 nm and 1600 nm AgNDs are 8, 123, 100, 291 and 176, respectively. The superior hydrogen evolution performance of this electrode is related to its well-structured surface and large real surface area. Graphical abstract: Three-dimensional 3D-AgNDs having different diameters were fabricated and characterized as promising electrode materials for electrolysis of water. Highlights: Three-dimensional 3D Ag nanodomes having different sizes were fabricated. The sizes of the nanodomes can be controlled by the method described in this study. Very well-structured and very uniformly distributed nanodomes were fabricated. The hydrogen evolution activity of nanostructures depends on their diameters. 1200 nm nanodomes exhibits excellent hydrogen evolution activity.